VARIATION OF SOME PROPERTIES OF THE STEM RADIUS AT RESONANT WOOD (Innovation in Woodworking Industry and Engineering design, 2026)
Many conditions need to be met for producing quality musical instruments. One of them is to have a consistency of structure and properties of wood. It is often difficult, especially for instruments in large dimensions. It is required to be cut large diameter trees.The article examines variations in the density, compressive strength and flexural strength and modulus of elasticity in the radius of the stem of the spruce. A section for the manufacture of musical instruments is studied in the factory „Kremona AD” – Kazanluk. A section has stayed in dry and heated place more than 12 years. The differences in the properties of the test pieces of juvenile, central and peripheral wood have been established.